Servant Leadership: Implementing the Principal's Role in Creating a Humanistic Education - Effendi, Yulius Rustan; Erb, Maribeth (Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This study aims to describe the leadership role of school principals based on spiritual-moral values in conditioning humanistic education. Background Problems: While servant leadership has been investigated from various angles, its application to principal leadership, primarily through a moral-spiritual lens, remains understudied. Novelty: This study underscores a gap in the literature on school principals' leadership, advocating for a spiritual-moral values approach to foster a humanistic school environment. Principals prioritize teachers' and students' interests, embodying servant leadership through active listening, open communication, and feedback acceptance. They also integrate moral, religious, and spiritual values into their leadership philosophy. Principal A hold holds regular open meetings, establishes communication channels, organizes activities promoting values, and implements anti-harassment policies. Principal B develops special programs and collaborates with teachers to infuse moral and spiritual aspects into subjects. Principal C integrates character education, offers teacher training on ethics, and encourages role modeling of ethical values. Research Methods: This research uses qualitative methods and a case study design, utilizing in-depth interviews, participant observation, and document analysis. The analysis includes a modified analytic approach with validation data through credibility, transferability, reliability, and confirmability assessments. Finding/Results: The study reveals that servant leadership fosters altruism, faithfulness, and morality, cultivating a humanistic learning environment and promoting personal awareness, psychological well-being, and ethical wisdom. Conclusion: In education, servant leadership promotes dialogue and humanistic values, emphasizing shared values over authority among school community members.